Interleukin-27 augments the inhibitory effects of sorafenib on bladder cancer cells - Cao,J.Y. (2017)
Both sorafenib and interleukin-27 (IL-27) are antineoplastic drugs. This study aimed to investigate the synergistic effect of these two drugs on bladder cancer cells. HTB-9 and T24 cells were stimulated with IL-27 (50 ng/mL), sorafenib (2 μM) or the synergistic action of these two drugs. The cells without treatment acted as control. Cell proliferation, apoptosis and invasion were measured by bromodeoxyuridine assay, flow cytometry and modified Boyden chamber, respectively. Simultaneously, both modified Boyden chamber and scratch assay were used to assess cell migration. Finally, the phosphorylation levels of key kinases in the Akt/mechanistic target of rapamycin (mTOR)/mitogen-activated protein kinase (MAPK) pathway, and expression levels of matrix metalloproteinase (MMP)-2 and MMP-9 were detected by western blot analysis. Stimulation with IL-27 or sorafenib repressed proliferation, migration and invasion but promoted apoptosis, and the effects were all enhanced by the combination of these two drugs in HTB-9 cells. The effect of the combined treatment on bladder cancer cells was verified in T24 cells. Additionally, the phosphorylation levels of AKT, mTOR and MAPK as well as the expression levels of MMP-2 and MMP-9 were all decreased by a single treatment of IL-27 or sorafenib, and further decreased by the combined treatment of these two drugs. The combination of IL-27 and sorafenib inhibited proliferation, migration and invasion and promoted apoptosis of bladder cancer cells compared with mono-drug treatment. Additionally, the AKT/mTOR/MAPK pathway might be implicated in the functional effects by down-regulations of MMP-2 and MMP-9.